Onsite clinic utilization and adherence in semiconductor employees at chronic disease risk - Boyoon Choi; Kyungim Kim; Hyun Jin Park; Yun-Kyoung Song; Jung Mi Oh (PLoS ONE, 2025)
Introduction The objective of this study was to evaluate the utilization and adherence of onsite clinics and identify the factors influencing them in semiconductor employees at risk of chronic diseases, including hypertension, diabetes, and dyslipidemia. Methods A cross-sectional study was conducted through a retrospective review of electronic medical records from onsite clinics at a South Korean semiconductor company. The study focused on employees who visited the onsite clinics between 2013 and 2016 due to the risk of chronic diseases including hypertension, diabetes, and dyslipidemia. Descriptive statistics assessed clinic utilization and adherence, while multivariable logistic regression identified influencing factors, adjusted for age, sex, work type, work shift, workplace, specific onsite clinic, diagnosis, and disease duration. Results Out of the 39,073 employees examined, 8,837 sought care at onsite clinics for managing chronic disease risks. The majority of these participants were male (88.2%) and predominantly aged in their 30s and 40s (84.6%). Among these individuals, 33.0% visited the clinics five or more times, and 28.5% filled prescriptions on two or more occasions. Chronic diseases were the second most common reason for onsite clinic visits. The average adherence to prescription as measured by the Proportion of Days Covered (PDC) was 0.61, with 40% of individuals showing a high adherence. Notably, older age and employment at workplaces located outside metropolitan areas were significant factors positively associated with both the utilization of onsite clinic services and adherence to prescribed treatments. Conclusion This study found that onsite clinics within a semiconductor company were actively utilized for managing chronic diseases, particularly among older employees and those in workplaces located in areas where medical access is limited compared to metropolitan areas. These findings highlight the potential role of onsite clinics in enhancing chronic disease management. Future research across a broader range of workplaces could further support and expand these insights.